Comparative effectiveness of gamified binocular treatment versus conventional patching for amblyopia: a randomized clinical trial - Chen, Ying; Chen, Yuzhen; Han, Xiao; Yang, Zijian (Frontiers in Medicine, 2025)
IntroductionAmblyopia, a prevalent visual disorder in children, leads to deficits in visual acuity, stereoacuity, and daily functioning. Conventional treatments such as eye patching, often encounter adherence challenges and relapse, especially in younger patients. This study investigates the effectiveness of a home-based, gamified binocular therapy (GBT), compared with traditional patching.MethodsA randomized controlled trial was conducted with 42 participants aged 4–8 years diagnosed with amblyopia from Sunshine Rehabilitation Center, Shanghai. Participants were randomly assigned to the GBT (n = 20) or the patching group (n = 22). Visual acuity (VA) and stereoacuity improvements were assessed at baseline, 1, 3, and 6 months.ResultsBoth groups demonstrated significant VA and stereoacuity improvements from baseline at 1 month. GBT participants exhibited faster initial VA improvement, with significant gains at 1 month compared to patching (mean difference = 0.072 logarithm of the minimum angle of resolution[logMAR], p = 0.0029). By 6 months, both groups showed similar improvements in VA (GBT: 0.19 ± 0.10 logMAR; patching: 0.23 ± 0.16; p = 0.156) and stereoacuity (GBT: 0.95 ± 0.76 log arcseconds; patching: 0.82 ± 0.59; p = 0.712). No significant adverse events were reported in either group.ConclusionThe study indicates that GBT is as effective as patching in improving amblyopic visual outcomes among Chinese children 4 to 8 years of age. These findings suggest that gamified binocular therapy could play an important role in personalized amblyopia treatment, with further studies needed to confirm long-term effects across diverse populations.